ROLE OF PHOSPHATE SOLUBILIZING BACTERIA (PSB) IN ENHANCING P AVAILABILITY AND PROMOTING COTTON GROWTH - M. A. Qureshi; Z. A. Ahmad; N. Akhtar; A. Iqbal; F. Mujeeb; M. A. Shakir (Journal of Animal and Plant Sciences, 2012)
Plant growth promoting rhizobacteria (PGPR) mediate the soil processes such as decomposition, nutrient mobilization, mineralization, solubilization, nitrogen fixation and growth hormone production. Microorganisms having the phosphate solubilizing capacity can convert the insoluble phosphates into soluble forms through the production of organic acids. Inoculation of seed with P-solubilizing microorganisms is a promising technique which may alleviate the deficiency of phosphorus. This bioavailability of soil inorganic phosphorus in the rhizosphere varies considerably with plant species and nutritional status of soil. A field experiment was conducted at Fiber Crops Section, Ayub Agricultural Research Institute (AARI) Faisalabad to assess the ability of P-solubilizing rhizobacteria to enhance the growth and yield of cotton. Isolation and screening of P-solubilizer on Pikovskaya’s medium was carried out at the Soil Bacteriology Section Faisalabad. The trial was conducted on clay loam soil with pH 8.3, EC 2.8 dSm-1, N 0.040 %, organic matter 0.75% and available P 10.3 mg kg-1 with three fertilizer levels viz. 120-30, 120-60, 120-90 kg NP ha-1 with and without P-solubilizer (Bacillus sp.) inoculum. Results revealed that bacterial inoculum produced significantly higher seed cotton yield 1630 as compared to 1511 kg ha-1. The highest seed cotton yield was observed at highest fertilizer level i.e. 1733 kg ha-1 with inoculum. The physical parameters like plant height, number of bolls per plant and boll weight and soil available P determined at regular intervals (30, 60, 90, days after sowing) was also found higher in the inoculated treatments. More exploration of this area of research should be carried out in different ecologies to compensate the mineral fertilizers
Keywords: Phosphate solubilizing bacteria (PSB); Available P; Bacillus; Phosphorus; cotton